Legitimacy in International Relations and the Rise and Fall of Yugoslavia - Williams, John. author. aut Link
X, 220 p.
Keywords: This book develops a conceptual model of legitimacy as a value-judgement in international relations in contrast to Weberian and legal approaches. The model is based on the interaction of the states-systemic value of order with a liberal ideal of the state and a free-market, liberal international economy. Whilst formulated as a principally Western model, the analysis of the rise and fall of Yugoslavia and the international response points towards a wider applicability as well as confirming the value of the concept as an analytical tool.